International Management - Fleming, Richard J. (Academy of Management Review, 1976)
The article reviews several books pertaining to the topic of international management, including “Comparative Management and Economic Progress,” by Richard N. Farmer and Barry M. Richman, “Multinational Management,” by F. T. Haner, and “Management in the Industrial World,” by Frederick Harbison and Charles A. Myers.